Responses of Pseudomonas aeruginosa to low oxygen indicate that growth in the cystic fibrosis lung is by aerobic respiration - Alvarez-Ortega, Carolina (2007)
Pseudomonas aeruginosa in the lungs of cystic fibrosis patients grows to high densities in mucopurulent material that is depleted in oxygen. Some have concluded that growth in these circumstances is dependent on anaerobic nitrate respiration. Here we present data in favour of the alternative hypothesis that microaerobic respiration is the predominant mode of P. aeruginosa growth in the cystic fibrosis lung. We found that P. aeruginosa strain PAO1 and a mucoid derivative of strain PAO1 each grew at dissolved oxygen concentrations of less than 3 µM. This is lower than the concentration of oxygen that has been measured in hypoxic cystic fibrosis mucous. A transcriptome analysis comparing cells grown under aerobic conditions (185 µM dissolved oxygen) with cells grown with 20 µM or 3 µM dissolved oxygen, or anaerobically with nitrate, revealed that overlapping sets of genes are expressed depending on oxygen availability. This suggests that P. aeruginosa responds to changes in oxygen concentration along a continuum rather than having a discrete low oxygen regulon. Any one of three high affinity terminal oxidases that P. aeruginosa encodes supported microaerobic growth. A triple mutant lacking all three of these oxidases failed to grow at low oxygen and formed abnormal biofilms.